Respostas

A melhor resposta!
  • Usuário do Brainly
2014-06-23T15:17:04-03:00
A)
(2 a^{5} +3)- ( a^{10}  - 9 ) =

2 a^{5}  + 3 - a^{10}  + 9=

2 a^{5} -  a^{10}  + 12

                                                  
b)
(3x-4)²+ (x+4)(x-4)- (4-x)²=
9x² -24x +16+x² -16- (16-8x+x²)
10x²-24x-16 +8x-x²=
9x²-16x -16

c)
A=(x+1)²+(x+1)(x-1)=  x²+2x +1+x²-1=2x² +2x

B=-2x(x+1)= -2x²-2x

A+B= (2x² +2x) + ( -2x²-2x)=2x² +2x -2x²-2x= 0

1)
a)
(3a+5)(3a-5)= 9a² -25
b)
A=9× 25² -25=9×625-25=5625-25=5600


2)
a)  a²-16
b)  9b²-9
c)  4 x^{4}  -16y²
d)   \frac{4 p^{6} }{9} - \frac{1}{4}

e)   \frac{ b^{4} }{25} -9


3)

(( \sqrt{501} +  \sqrt{499} )( \sqrt{501} -  \sqrt{499} )


4)
x²-y²=24                  x+y=12                x=12-y
(12-y)²-y²=24

144-24y+y²-y²=24
-24y=24-144
-24y=-120
24y=120
y= \frac{120}{24}

y=5
como x=12-y
  x=12-5
x=7

então x-y
7-5=2
1 5 1